Optimizing the Choice of Means of Transport using Operational Research - Piotr Gorzelanczyk; Henryk Tylick; Tomáš Kalina; Martin Jurkovič (Communications - Scientific letters of the University of Zilina, 2021)
This study focuses on the issue of choosing a means of transport on the PilaWarsaw route by four groups of recipients. Representative sample consists of a student, a family with two children, a business client and a pensioner. The choice of the means of transport depends on various criteria resulting from the preferences of the users of the means of transport. The following criteria emerged from the survey results as a priority: transport time, transport cost, comfort and safety of travel, availability of means of transport, necessity or absence of transfers, cost of luggage transport and punctuality of means of transport. Selected preferences were assigned weightings based on the evaluation of a panel of experts in the field of expertise. In order to select the means of transport to implement the transport task, multi-criteria optimization method was used.